Can FMA (Noise) 1989 prevent occupational noise-induced hearing loss? an evaluation using fault tree analysis - M. A., Ahmad; Razali, Ailin (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Occupational health practitioners in our country were heartened following the gazettement of the new regulation with regard to occupational noise exposure in alignment with the Occupational Safety and Health Act (OSHA 1994) by the Attorney General’s Chamber in early June this year. It took almost two decades for the Factory Machinery Act (Noise Exposure) to be finally revoked.1,2The new regulation is expected to play a crucial role in further curbing occupational noise-induced hearing loss (NIHL), a disease that has consistently been the most notified to Department of Occupational Safety and Health (DOSH) and one of the most compensated of occupational diseases Social Security Organization (SOCSO). This piece is a brief summary of the regulation and its’ impact on the relevant players and stakeholders in the occupational safety and health fraternity.